Health status and health behaviour of the Hungarian homeless people - Emese Nagy-Borsy; Zsolt Vági; Petra Skerlecz; Blanka Szeitl; István Kiss; Zsuzsa Rákosy (BMC, 2021)
Abstract Background Homelessness has risen recently in Europe, but there is lack of comprehensive health data on this population. Our aim was to characterize the health of the Hungarian homeless population. Methods We performed a health survey with 453 homeless individuals. The results were compared to the age and sex standardized data of the general Hungarian population and its lowest income quintile from the European Health Interview Survey 2014. The differences by the ETHOS classification within the homeless population were also studied. Results Significantly fewer homeless people reported good health status than in the general population or in its lowest income quintile (p< 0.001). Of the participants 70% had at least one chronic disease, only 41% of them visited a GP and 35% took medication in the previous 12 months. While 59% of the lowest income quintile and 50% of the general population had at least one chronic disease, almost all of them visited a physician and took medication. The highest prevalence of morbidity (80%) and multimorbidity (46%) was reported in the houseless group. The majority of the homeless people were current smokers, the prevalence was much higher than in the two reference populations (p< 0.001). The prevalence of heavy drinkers was the highest among the roofless participants (40%). Conclusions Homeless people have much poorer health and they utilize health services less than the most disadvantaged quintile of the general population. There is a clear social gradient within the homeless population, as well, which calls for integrated approaches for specific interventions to improve their health.